Pengaruh Manajemen Laba, Struktur Kepemilikan, dan Struktur Dewan Terhadap Nilai Perusahaan Manufaktur yang Terdaftar Di Bursa Efek Indonesia - Sarah Ayu Larasati; Henny Setyo Lestari (Universitas Batanghari, 2022)
This study aims to determine the effect of earnings management, ownership structure, and board structure on firm value. The dependent variable used is Tobin's Q Ratio. While the independent variables used are earnings management, institutional ownership, managerial ownership, independent board of commissioners, and board size. The data in this study uses annual reports from 37 manufacturing companies listed on the Indonesia Stock Exchange in 2017-2021. The data collection technique used purposive sampling technique obtained from the web www.idx.co.id and each website of the sample company. Power processing uses panel data regression and the results show that earnings management, institutional ownership, and managerial ownership have an effect on firm value. While the independent board of commissioners has an effect but is not significant on the value of the company. And the size of the board has no effect on firm value. The results of the F test show that the independent variables simultaneously affect the dependent variable. The results of the coefficient of determination (R2) indicate that the ability of the independent variable is quite large in explaining the dependent variable.